Evaluation of an Anglo-Centric ELT Textbook in Bangladeshi Context: A Case Study - Kabir, Md Humayun (IIUC Studies, 2014)
With the advancement in human civilization and human understanding we are now bold enough to ask the value of and rationale for something imposed on us by any quarter. If carefully observed, it is evident that BANA (Britain, Australia and North America) country materials have dominated the ELT (English Language Teaching) related field for quite a long time. We anxiously notice that in these materials the socio-cultural background of the vast community of ESL/EFL users (learners and teachers) is grossly ignored. Since the learners background knowledge i.e. schema is an issue of paramount importance in ELT, in this study our attempt is to assess and justify the suitability of the Anglo-centric ELT textbooks titled Foundation English Course (FEC) Book-I&II which is designed to teach the students of REC (Remedial English Course) programme at IIUC (International Islamic University Chittagong). DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20399 IIUC Studies Vol.8 December 2011: 11-26